Adaptation of ethnic cuisine attributes, preparation and formation of common acceptable cuisine / Mohd Zulhilmi Suhaimi - Suhaimi, Mohd Zulhilmi (2013)
The concept of common acceptable cuisine usually discussed in the multi cultural/ethnic nation as it represents the process of sharing acceptable cuisine among the ethnic groups. The common acceptable cuisine also consider as a precursor that takes place in the process of constructing the national food identity within ethnic groups in the multicultural countries which denotes to social integration, reputable and nation building. The practice on cultural adaptation of cuisine is believed enhances the process of sharing the common acceptable cuisine which in turn promoting inter-ethnic social cohesion. In this sense, the adaptation of certain ethnic cuisine through types of food, methods of cooking, ingredients and eating decorum by ethnic groups and mediates by preparation is believed creating or ehancing the process of formation on common acceptable cuisines in a multicultural country. In line with this, Malaysia as the multicultural country without doubt is continuing to experience a cross-culturing processes among the ethnic groups in term of culture, including cuisine therefore the concept that have been highlighted can suitably be investigated. Owing to that, this study empirically investigate the adaptation level of Malay, Chinese and Indian chefs on each other ethnic cuisine attributes through preparation toward the beliefs of formation on common acceptable cuisine in Malaysia. Using the quantitative approach, the selected Malay, Chinese and Indian^ chefs that work and experiences in various food establishments like hotels, restaurants, catering operations and other related operation within the Kuala Lumpur and Selangor (Shah Alam and Petaling Jaya) were suveyed. The information required was gathered through self-reported and self-administered questionnaire. Through frequencies, descriptive (mean score) and inferential statistic (standard multiple regressions) analyses, some useful insights on the issue investigated were obtained. A very clear picture emerged that most of the three major ethnic chefs, Malay, Chinese and Indian were having a common view on the process of adaptation of ethnic cuisine attributes (types of food, method of cooking, ingredients and eating decorum) and no doubt believing preparation or practicing of it is giving advantages to the formation of common acceptable cuisine for the country. These optimistic indications therefore carry varying consequences and implications for chefs, those individual closely associated with food preparation and the relevant authorities.